The Influence of Palembang Arts and Culture on the Development of Digital Literacy and Communication Creativity of Students at UIN Raden Fatah Palembang - Ningsih, Chairunnisah Putri Ayu; Yulia Anggraini, Riska; Belagustin, Anggita; Triana, Triana (Wardah, 2025)
This study originates from the need for students to develop 21st-century competencies, particularly digital literacy and communication creativity, amidst the rapid transformation of information technology. Palembang’s arts and culture, as a local heritage rich in aesthetic and philosophical values, are considered to have strategic potential in strengthening students’ identity, creative expression, and digital communication skills. This research aims to analyze the influence of Palembang arts and culture on the development of digital literacy and communication creativity among students at UIN Raden Fatah Palembang and to assess the extent to which local cultural values can be integrated into digital-based learning. Employing a mixed methods approach with a sequential explanatory design, the study began with quantitative data collection through questionnaires distributed to 75 students from the Faculty of Da'wah and Communication and the Faculty of Social and Political Sciences, followed by qualitative data collection through in-depth interviews and observations of cultural and digital communication activities. Data were analyzed using the Miles and Huberman model through data reduction, presentation, and conclusion drawing. The results show that Palembang arts and culture have a positive and significant effect on improving students’ digital literacy and communication creativity. Students actively involved in local cultural activities demonstrate greater abilities in utilizing digital media creatively, ethically, and contextually. Cultural values such as cooperation, originality, and aesthetics encourage the creation of innovative digital content rooted in local identity. Qualitative findings further reveal that social media serves as a strategic space for students to express cultural identity and expand positive communication networks. The study concludes that integrating Palembang arts and culture into digital literacy activities can serve as a model for local wisdom–based education relevant to the digital era. Its implications highlight the importance of curriculum design and institutional support that combine local culture with technology to nurture a creative, character-driven, and culturally grounded young generation.